Myopia progression after cessation of low‐dose atropine eyedrops treatment: A two‐year randomized, double‐masked, placebo‐controlled, cross‐over trial. Issue 2 (23rd August 2022) - Wei, Shifei; Li, Shi‐Ming; An, Wenzai; Du, Jialing; Liang, Xintong; Sun, Yunyun; Gan, Jiahe; Bai, Weiling; Tian, Jiaxin; Cai, Zhining; Yin, Lei; Wang, Ningli
Abstract: Purpose: The purpose of the study was to evaluate myopia progression and axial elongation after stopping 0.01% atropine eye drops through a 2‐year cross‐over study. Methods: This study was a randomized, double‐masked, placebo‐controlled, cross‐over trial in mainland China. 220 children aged 6–12 years with spherical equivalent range of −1.00 D to −6.00 D in both eyes were enrolled in Phase 1 for 1 year. Children who had completed the first year's follow‐up continued in the second phase. In Phase 2, the placebo group was crossed over to the 0.01% atropine group (referred to as the 'placebo‐atropine group'), and the 0.01% atropine group was crossed over to the placebo group (referred to as the 'atropine‐placebo group'). All children underwent the examination of cycloplegic refraction and axial length at a 6‐month interval. Only data from right eyes were included in analysis. Results: One hundred thirty‐three subjects completed 2 years of follow‐up. In the first year, the mean myopia progression in atropine‐placebo group was 0.21 ± 0.08 D slower than that in placebo‐atropine group. After cross‐over treatment, the mean myopia progression in atropine‐placebo group was 0.22 ± 0.07D faster than that in placebo‐atropine group in the second year. Over 2 years, the mean myopia progression was −1.26 ± 0.66D and −1.25 ± 0.70D in the atropine‐placebo and placebo‐atropine groups ( p  = 0.954). Conclusions: The difference in myopia progression between atropine‐placebo group and placebo‐atropine group in Phase 1 was similar to Phase 2 during the cross‐over treatment. Through our cross‐over trial, the results suggest that there is no rebound effect after using 0.01% atropine eye drops to prevent progression of myopia.